ANALISIS USAHATANI LABU KUNING DI DESA SINGSINGON RAYA, KECAMATAN PASSI TIMUR, KABUPATEN BOLAANG-MONGONDOW - Lina Tini Pendong; Oktavianus ., Porajouw; Lyndon R. J. Pangemanan (AGRI-SOSIOEKONOMI, 2017)
This study aims to analyze the cost and income of pumpkin farming in Singsingon Raya Village, East Passi District. The study was conducted from January to February 2017. The data used were primary and secondary data. Primary data through interviews using questionnaires to 15 respondents and secondary data obtained from Singsingon Raya Village Office. This analysis uses descriptive analysis. The results showed that the cost used for the largest pumpkin laboratory is labor cost and transportation cost of 87.28 %. In the marketing of pumpkin, farmers get large enough revenue so that farmers earn substantial income. The results can be seen from the total average production cost of Rp 4,012,238.00 / Ha with average revenue of Rp 21,159,420.00 / Ha of farmers earning income of Rp 17,147,182.00 / Ha. Analysis of return cost ratio get value > 1 so that pumpkin profitable for farmers and break even point analysis results showed that pumpkin farming is at break even point.